Design Of Master Mask Film, Fabrication Of PDMS Mold And Fabricate Uv Led Curing Unit To Test Imprint Capability Of Roll-To-Plate Nanoimprint Lithography System - Ghazali, Mohamad Hazwan Mohd (Universiti Sains Malaysia, 2017)
Current optical lithography method still cannot cope with the increasing demands from the industry especially electronics and biomedical industry. Not just it is low throughput; it is also difficult to conduct, not to mention the end product of this method is not as accurately as anticipated. Due to these limitations, lots of other alternatives are being developed and one of it is nanoimprint lithography (NIL). NIL is a better alternative to the conventional lithography method as it is simpler, cheaper and has higher throughput. Roll to plate NIL is one of the many NIL techniques and it will be focused in this project. The main objectives of this study is to modify the roll to plate NIL machine which is still under development so that it can be a complete machine capable of both large area mold making and roll to plate NIL process. This project can be divided into two parts; modifications of the roll to plate NIL machine and NIL process. Modifications include installation of heating element, UV curing station, doctor blade mechanism, seamless mold station, motors and other supporting components. Because the roll to plate NIL machine is still not fully complete, NIL process was done using plate to plate NIL machine to test its concept. Although the machine used is different, the concept of NIL is still the same. First of all, the designed patterns are directly transferred from master mask film to microscope glass, aided by UV rays. Then, the patterns are replicated to PDMS mold before being imprinted to silicon substrate using plate to plate NIL machine. At first, the designed patterns were successfully imprinted on the silicon substrate but it was less accurate as some patterns cannot be seen. In the second experiment, the new structures has been successfully imprinted with better results along with its dimensions.